Performance efficiency of waqf institution in Malaysia / Nor Tasik Misbahrudin - Misbahrudin, Nor Tasik (2018)
Waqf is defined as a voluntary charity that cannot be disposed of and the ownership cannot be transferred once it is declared as waqf assets. Waqf institution is one of the important instruments in Muslim's economic development. The roles of waqf not only help Muslim ummah yet the whole community. Waqf can be used as tools to improve wellbeing, poverty alleviations and provide basic needs to the poor and less privileged which they cannot get such as access to health and education. Since waqf institution act as intermediaries between giver (waqif) and beneficiaries (Mawquf 'Alayh), this institution has to perform efficiency in order to maintain the public confident towards them. Consequently, efficiency of waqf institution is the main indication of organization on achieving the objectives. Failure to achieve these objectives will reduce public confidence towards the ability of waqf institutions to manage waqf assets. Despite a lot of issues on waqf, there were still very few studies done to determine the exact usage of waqf assets. Furthermore, most studies found only focused on problems of management and administration of waqf properties and documentation. This study utilized secondary data sources which are library research and information from annual report method. Thus, this study examines the efficiency of waqf institutions in Malaysia by utilizing Data Envelopment Analysis (DEA) and using five states as Decision Making Unit (DMU). In addition, this study also determined the most influential efficiency dimensions of Pure Technical Efficiency (PTE) and Scale Efficiency (SE) towards waqf institutions in Malaysia. The result indicated that only Selangor and Johor are efficient throughout the years of analysis while other states namely Pulau Pinang, Melaka and Federal Territory are far from the frontier level. It also found that as general the inefficiency score of waqf institutions is contributed by the PTE rather than SE. Hence, this study suggested that the role of government in federal and states level in supporting waqf institutions must be strengthened to improve their performance efficiency. Cooperation among all parties and stakeholders is crucial for the betterment of the institutions to ensure the objectives of wa^/"endowment are achieved.